Hubungan Faktor-Sosio Demografis dengan Perilaku Beresiko Tertular HIV AIDS pada TKI di Kabupaten Lombok Timur - I Made Eka Santosa (Jurnal PRIMA, 2015)
Human Immunodefficiency Virus(HI V) is the virus that causes Acquired Immuno Deficiency Syndrome (AIDS) that can affect anyone regardless ofsex, occupation, ethnicity, religion, economic status or social status. But there are groups at high risk of contracting HI V/ AIDS. One of the vulnerable population groups to HI V/ AIDS in East Lombok regency is the Indonesian Migran Workers ( Tenaga Kerja Indonesia / T KI). Mobility and migration on migrant workers vulnerable to HI Vin/ ection creates conditions that are supported by high-risk behavior for transmission of HIV / AIDS. Researchers wanted to determine associated between sosio - demografis factors with risk behaviors of HIV/ AIDS on migrant workers in East Lombok regency. This research is a quantitative analytic approach to study the dynamics crossectional correlations between risk factors with efects, with data collected simultaneously at any one time. Sampling technique used was convenience sampling in all districts in East Lombok for respondents who met the inclusion criteria. Instruments used in this study is a questionnaire are modified from the Behavior Surveillance Survey (SSP) in 2005. Of the 461 respondents surveyed, this study shows that there are associated between sosio-demografissfactors with risk behavior ofcontractin g HI V/ AIDS to migrant workers in East Lombok include: age, gender, marital status, education level, and income. All variables have a correlation value was less than the value ofalpha 0. 05. Only one variable has a correlation value greater than Al/a 0.05 that is a work type meaningful no relationship between work type with risk behavior of HI V/AIDS transmission. The results ofthis study is expected to be used as input for the stakeholders to pay more attention to aspects of the risk of transmission of HIV / AIDS on the worker.Key words : Indonesian Migrant workers, risk behavior HIP / AIDS